The role of Nurses in anemia associated with chronic kidney disease: an integrative review (Research, Society and Development, 2020)
This study objective is to identify in the literature the role of nurses in caring for patientes with anemia associated with Chronic Kidney Disease. It is an integrative review of the literature carried out in the databases of Latin American and Caribbean Literature in Health Sciences, Medical Literature Analysis and Retrieval System Online and Excerpta Medica database. Articles in Portuguese, English and Spanish were included, in any period of time and that presented nursing care and the role nurses in anemia associated with Chronic Kidney Disease. The results emphasize the role of the nurse in the development and leadership of care models and guidelines / protocols, revealing the importance of this professional in the planning and execution of nursing care. It is concluded that the Nursing Care Systematization and the Nursing Process linked to the use standardized languages, provide a structure for the organization of information and management of nursing care directed to patients with anemia associated with Chronic Kidney Disease.